Multiplex biomarker-based ELISA enables early detection of Mycobacterium avium subspecies paratuberculosis-specific antibodies comparable to IFN-γ testing - Chiu, Shih-Jiuan; Bugde, Piyush; Kinga, Andrea; Bannantine, John P.; Liggett, Simon; Dukkipati, Venkata Sayoji Rao; Furuya, Yoichi (Frontiers in Veterinary Science, 2026)
Johne’s disease, caused by Mycobacterium avium subspecies paratuberculosis (MAP), continues to pose a major global challenge for the livestock industry due to its long subclinical phase and the limitations of current diagnostics. Commercial antibody-based ELISA tests often fail to detect early-stage infections, while interferon (IFN)-γ assays, though considered more sensitive at early stages, are costly and logistically complex. We present a novel multiplex ELISA that incorporates multiple MAP antigens for the detection of MAP-specific IgG antibodies in bovine serum and milk. Using well-characterized positive and negative cohorts, the assay demonstrated strong concordance with IFN-γ responses and outperformed commercial monoplex ELISA kits (IDEXX and IDVET). Our findings support its potential as a practical, high-throughput alternative for early detection of MAP-specific antibodies and for herd-level disease management.